Studentsâ Perceptions of Web-based Media Practicality on Cell Biology Course - Amelia, Trisna; Asikin, Nurul (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Cell Biology is one of the difficult subjects because of its microscopic and abstract study. It requires lecturers ability to present concepts of cell biology concretely so that students can achieve learning outcomes. Web-based media is considered appropriate to the course. This media may provide visualization of study objects through video streaming, micrograph images, or links to relevant articles. It has been conducted a descriptive researchto describedstudents perceptions of web-based media practicality on Cell Biology course. The data obtained from questionnaires and unstructured interviews to students. Based on the research, it was known that students agreed the web-based media is practically used and able to streamline the learning time. Students believed that web-based media provides the motivational and cognitive function in learning. On the other hand, students argued that slow internet connections make it difficult for them to access video learning on the media. It can be concluded that students had positive perceptions of web-based media practicality.